CYP2C19 genetic polymorphism in the Vietnamese population - Vu, Nhung Phuong; Nguyen, Hoa Thi Thanh; Tran, Ngoc Thi Bich; Nguyen, Ton Dang; Huynh, Hue Thi Thu; Nguyen, Xuan Thi; Nguyen, Duong Thuy; Nong, Hai Van; Nguyen, Ha Hai (Annals of Human Biology, 2019)
Background: Genetic polymorphism of CYP2C19 has been shown to affect enzyme activity and thereby contribute to inter-individual variability in drug metabolism and response. The complete genetic variation of CYP2C19 in Vietnam still remains obscure even though data of common alleles in Vietnamese Kinh have been reported. Aim: To establish the extent of CYP2C19 polymorphism in Vietnamese. Subjects and methods: The promoter and all nine exons of CYP2C19 in 100 healthy unrelated Vietnamese Kinh subjects were sequenced. Additionally, the CYP2C19 variants, *2, *3 and *17 were analysed by RFLP-PCR in 275 subjects of four minor ethnic groups in Vietnam (Tay, Muong, H'Mong and Nung). Results: In 100 Kinh subjects, the percentages of CYP2C19*1, CYP2C19*2, CYP2C19*3 and CYP2C19*17 alleles were 76%, 20.5%, 2.5% and 1%, respectively. Three novel variants in introns 2, 5 and 8 had no impact on mRNA splicing according to the Human Splicing Finder. The prevalence of CYP2C19*17 in Vietnamese Kinh was significantly lower compared with figures found in Western Asia and Europe, while CYP2C19*2 frequency was statistically higher than that in Western Asia and several countries in Europe. The frequency of CYP2C19*2 in Kinh was significantly lower than in the other four ethnic minorities. Conclusion: These results provide information on CYP2C19 polymorphism in the Vietnamese population, which could be useful for optimising drug therapies and precision medicine studies.